2021
DOI: 10.3389/fendo.2021.631384
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Sex-Specific Endocrine Responses to Reproduction and Parental Care

Abstract: Hormones mediate physiological and behavioral changes in adults as they transition into reproduction. In this study, we characterize the circulating levels of five key hormones involved in reproduction in rock doves (Columba livia): corticosterone, progesterone, estradiol, testosterone, and prolactin using univariate and multivariate approaches. We show similar patterns as previous studies in the overall patterns in circulating levels of these hormones, i.e., testosterone (males) and estradiol (females) high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…During the poultry breeding season, reproductive hormones that are important for parental behaviour and initiation of egg production include LH and FSH, which are released by the anterior pituitary, and testosterone, estradiol (E2), and progesterone produced by the ovaries (Buntin, 1996; Ramakrishnan et al, 2007). Consistent with previous studies, in middle and late lactation—with the maturation of follicle development—the plasma E2 and progesterone levels in female pigeons gradually increased (Austin et al, 2021; Dong et al, 2013; Xie et al, 2019). Levels of LH and FSH produced by the pituitary and testosterone secreted by the ovary gradually decreased in middle and late lactation.…”
Section: Discussionsupporting
confidence: 88%
“…During the poultry breeding season, reproductive hormones that are important for parental behaviour and initiation of egg production include LH and FSH, which are released by the anterior pituitary, and testosterone, estradiol (E2), and progesterone produced by the ovaries (Buntin, 1996; Ramakrishnan et al, 2007). Consistent with previous studies, in middle and late lactation—with the maturation of follicle development—the plasma E2 and progesterone levels in female pigeons gradually increased (Austin et al, 2021; Dong et al, 2013; Xie et al, 2019). Levels of LH and FSH produced by the pituitary and testosterone secreted by the ovary gradually decreased in middle and late lactation.…”
Section: Discussionsupporting
confidence: 88%
“…Slightly elevated levels of progesterone during this period are consistent with findings from other bird species during egg-laying (e.g. [93,103]). It is therefore rather surprising that, in white-browed coucals, progesterone levels tended to be higher during the pre-breeding period than during the mating period.…”
Section: Discussionsupporting
confidence: 88%
“…It is therefore rather surprising that, in white-browed coucals, progesterone levels tended to be higher during the pre-breeding period than during the mating period. Low levels of progesterone in the incubation phase of male black coucals are consistent with low-progesterone concentrations of incubating females of other species [93,103,104]. However, the hormonal regulation of incubation behaviour requires a suite of interacting hormones [104] and further studies including measurements and experimental manipulations of sex steroids and prolactin in males would be required to elucidate the hormonal regulation of incubation behaviour in male coucals.…”
Section: Discussionmentioning
confidence: 74%
“…Taken together, these results indicated that the crop of parent pigeons undergoes dramatic changes in morphology during the breeding stages, in which each sex shows varying degrees of change, accompanied by a transition in parental behavior. This reflects a change in the division of labor between sexes during the breeding stages which may be related to shifts in gonadal steroid hormone levels [ 11 , 12 ]. For example, in female pigeons, serum estradiol concentration increases dramatically in the later stages of feeding [ 13 ], possibly to prepare for the next breeding stages.…”
Section: Resultsmentioning
confidence: 99%